Revealing lecturer’s paralinguistic attribution: How the visual manner contributes to students’ non-cognitive skills - Sumekto, Didik Rinan; Setyawati, Heny (Indonesian Journal of Applied Linguistics, 2020)
Classroom-based communication requires an appropriate contribution from lecturer’s perspectives to address students’ non-cognitive skills. This study examines the paralinguistic attribution contributions deriving from lecturer’s visual manner. Of 504 pre-service English teachers, 120 freshmen participated in this study. Data collection used the questionnaire through a random sampling selection from lecturer’s writing instruction. Data analysis used the multiple regression analyses with the significance level (p-value) of .05. The findings exhibited that lecturer’s paralinguistic attributions, namely: articulation (t = 1.073; p = .286), sonority (t = 2.896; p = .005), loudness (t = 3.433; p = .001), facial expression and lips setting (t = 1.097; p = .275), and gesture (t = 2.323; p = .022) contributed a significant influence towards the writing class instruction positively. The effectiveness of the paralinguistic attributions contributed 45.5% from overall findings shown in this study, in which the regression analysis statistically addressed that F = 19.017, R² = .455, and p .05. This study concludes the existence of the paralinguistic attributions accommodates freshmen’s learning maturation in lecturer’s instructional modes.